(untitled) (Scientific journal of the Fergana State University, 2024)
The article aims to study the content of the concept of “Safe and secure Mahalla” in new Uzbekistan in recent years, the importance of the “Safe Mahalla” system in the structure of self-government, the issues of preparing the population of the mahalla for such situations in emergency situations, the concept of “Safe Mahalla” for the prevention of crime in mahallas. During the research, methods of comparative and critical study of political and pedagogical literature on the problem, analysis of statistical data were used. According to the results of the study, proposals have been made in our country for the implementation of the ”prosperous and safe Mahalla" system in mahallas.